Case Series of Three Patients with Rifampicin-Induced Thrombocytopenia - M.T, Chandramouli (Journal of Health and Allied Sciences NU, 2020)
Life-threatening adverse reactions of antitubercular drugs are uncommon; however, thrombocytopenia is one such rare complication encountered with rifampicin, isoniazid, ethambutol, and pyrazinamide. Rifampicin is the most effective drug and its use in the tuberculosis treatment led to the emergence of modern and effective short-course regimens. I am reporting case series of three patients with pulmonary tuberculosis presented with rifampicin-induced thrombocytopenia.
Keywords: tuberculosis; rifampicin; thrombocytopenia; purpura; antiplatelet antibody